Architectural Study of Koca Sinan Pasha Mosque at Kaçanik, Kosova - Orges Drançolli (Journal of Islamic Architecture, 2022)
Koca Sinan Pasha Mosque is one of the oldest classical mosques built in Kosova during the reign of the Ottoman Empire (1389-1912). The mosque bore the name of its donor and was completed in 1594/95. It is located in a small town in the southern part of the country, in Kaçanik. Regarding its compositional scheme, the monument belongs to the examples of Ottoman-style mosques in the Balkans with local elements. Its compositional scheme comprises a prayer hall, portico, and a minaret. The paper focuses on a brief history of the Koca Sinan Pasha, the history of the mosque, architecture, pictorial and sculptural decorations, current condition, and the monument's surroundings. By doing so, the paper helps identify the challenges that the mosque faced during its existence, as well as changes in the structure of the building and its decorations that occurred with time. The study relies on the existing monument as the primary source of information. However, the documentation of the Institute for the Protection of Cultural Monuments of Kosova and the relevant literature that directly or indirectly deals with the issue in question has also been used. The study is accompanied by architectural visualization and photographs of the mosque's exterior and interior. The Paper aims to help study, promote and display the mosque's value to a wider audience